2022
DOI: 10.1186/s10020-022-00574-6
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide regulates Th17/Treg balance via PI3K/Akt/FoxO1 pathway in db/db mice

Abstract: Background The T helper 17 (Th17)/T regulatory (Treg) cell imbalance is involved in the course of obesity and type 2 diabetes mellitus (T2DM). In the current study, the exact role of glucagon-like peptide-1 receptor agonist (GLP-1RA) exenatide on regulating the Th17/Treg balance and the underlying molecular mechanisms are investigated in obese diabetic mice model. Methods Metabolic parameters were monitored in db/db mice treated with/without exenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Th17 cells play a role in promoting in ammation and immune responses, whereas Tregs act as immunosuppressors. There may be a link between the onset and progression of DM (types 1 and 2) and an imbalance between Tregs and Th17 cells [43][44][45] . A population-based study conducted in Finland revealed a signi cant correlation between T1D and other autoimmune diseases, including GD 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells play a role in promoting in ammation and immune responses, whereas Tregs act as immunosuppressors. There may be a link between the onset and progression of DM (types 1 and 2) and an imbalance between Tregs and Th17 cells [43][44][45] . A population-based study conducted in Finland revealed a signi cant correlation between T1D and other autoimmune diseases, including GD 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that after binding insulin in the liver, the insulin receptor autophosphorylates and goes on to phosphorylate several insulin receptor substrates, thereby activating classical IRS signaling pathways, including the phosphatidylinositol 3-kinase (PI3K)-phosphatidylinositol-dependent kinase (PDK)-protein kinase B (AKT) signaling pathway 21 . However, we found that protein levels of p-PI3K/PI3K and p-AKT/AKT were signi cantly lower in the livers of diabetic mice than in the livers of db/m mice, as detected by western blotting (Fig.…”
Section: Insulin Resistance Induced Hepatic Lipid Deposition In Db/db...mentioning
confidence: 99%
“…19 Th17 cells are also elevated in murine PBMCs and adipose tissue following high-fat diet feeding. 20,21 The Th17 population in adipose tissue of obese mice is activated by CD11c + DC cells, demonstrating the importance of innate/adaptive immune cell cross talk in obesity-associated inflammation. 20 At the same time, obesity reduces the T regulatory cell (Treg) population in visceral fat, while Treg frequency in the spleen of the same animals was similar to animals on control diet.…”
Section: T-cell Infl Ammati On In MI Ce With Ob E S It Ymentioning
confidence: 99%
“…Surprisingly, single‐cell RNA analysis showed that there is no change in Th1 and Th2 populations in adipose tissue of obese mice when compared to lean mice 19 . Th17 cells are also elevated in murine PBMCs and adipose tissue following high‐fat diet feeding 20,21 . The Th17 population in adipose tissue of obese mice is activated by CD11c + DC cells, demonstrating the importance of innate/adaptive immune cell cross talk in obesity‐associated inflammation 20 …”
Section: T‐cell Inflammation In Mice With Obesitymentioning
confidence: 99%